Best practice in radiofrequency denervation of the lumbar facet joints: a consensus technique. Issue 1 (February 2020) - Eldabe, Sam; Tariq, Anisah; Nath, Sherdil; Gulve, Ashish; Antrobus, Hugh; Baloch, Mohjir; Buczkowski, Piotr; Collighan, Neil; Fernandez, Tacson; Fritz, Ann-Katrin; Humble, Stephen; Huygen, Frank; et al.
Background: Radiofrequency denervation is used to treat selected people with low back pain. Recent trials have been criticised for using a sub-optimal intervention technique. Objectives: To achieve consensus on a best practice technique for administering radiofrequency denervation of the lumbar facet joints to selected people with low back pain. Study design: A consensus of expert professionals in the area of radiofrequency denervation of the lumbar facet joints. Methods: We invited a clinical member from the 30 most active UK departments in radiofrequency pain procedures and two overseas clinicians with specific expertise to a 1 day consensus meeting. Drawing on the known anatomy of the medial branch, the theoretical basis of radiofrequency procedures, a survey of current practice and collective expertise, delegates were facilitated to reach consensus on the best practice technique. Results: The day was attended by 24 UK and international clinical experts. Attendees agreed a best practice technique for the conduct of radiofrequency denervation of the lumbar facet joints. Limitations: This consensus was based on a 1 day meeting of 24 clinical experts who attended and took part in the discussions. The agreed technique has not been subject to input from a wider community of experts. Conclusions: Current best practice for radiofrequency denervation has been agreed for use in a UK trial. Group members intend immediate implementation in their respective trusts. We propose using this in a planned Randomised Controlled Trial (RCT) of radiofrequency denervation for selected people with low back pain.